The SNO+ experiment. (25th August 2021) - Albanese, V.; Alves, R.; Anderson, M.R.; Andringa, S.; Anselmo, L.; Arushanova, E.; Asahi, S.; Askins, M.; Auty, D.J.; Back, A.R.; Back, S.; Barão, F.; et al.
Abstract: The SNO+ experiment is located 2 km underground at SNOLAB in Sudbury, Canada. A low background search for neutrinoless double beta (0) decay will be conducted using 780 tonnes of liquid scintillator loaded with 3.9 tonnes of natural tellurium, corresponding to 1.3 tonnes of [130]Te. This paper provides a general overview of the SNO+ experiment, including detector design, construction of process plants, commissioning efforts, electronics upgrades, data acquisition systems, and calibration techniques. The SNO+ collaboration is reusing the acrylic vessel, PMT array, and electronics of the SNO detector, having made a number of experimental upgrades and essential adaptations for use with the liquid scintillator. With low backgrounds and a low energy threshold, the SNO+ collaboration will also pursue a rich physics program beyond the search for 0 decay, including studies of geo- and reactor antineutrinos, supernova and solar neutrinos, and exotic physics such as the search for invisible nucleon decay. The SNO+ approach to the search for 0 decay is scalable: a future phase with high [130]Te-loading is envisioned to probe an effective Majorana mass in the inverted mass ordering region.